1961
DOI: 10.1152/ajplegacy.1961.201.4.639
|View full text |Cite
|
Sign up to set email alerts
|

Glucose biokinetics in sheep

Abstract: The transfer rate of the glucose pool in sheep was estimated by methods using labeled glucose. Transfer rates ranged from 0.28 to 0.39 g/hr/kg3/4 when estimated 1 or 16 hr after feeding, but were only 0.18 and 0.20 g/hr/kg3/4 when estimated 96 hr after feeding. Comparable values calculated from data in the literature for rats, dogs, and man range from 0.25 to 0.40 g/hr/kg3/4 at 16 hr after feeding, although they are higher for rats only 4 hr after feeding (0.89 g/hr/kg3/4). Comparison of postabsorptive values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1963
1963
1991
1991

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Examination of arterial and portal blood in sheep has indicated that propionate and butyrate are almost completely removed by the liver under normal feeding conditions, but substantial quantities of acetate appear in peripheral blood (Annison, Hill & Lewis, 1957). A substantial glucose turnover in sheep has been indicated (Annison & White, 1961;Kronfeld & Simesen, 1961), focusing attention on the nature of glucose precursors in this species since very little glucose is absorbed from the alimentary tract. Propionate is well recognized as a source of glucose, but the possibility of butyrate and, to a less extent, of acetate being a precursor of glucose has been the subject of much speculation.…”
mentioning
confidence: 99%
“…Examination of arterial and portal blood in sheep has indicated that propionate and butyrate are almost completely removed by the liver under normal feeding conditions, but substantial quantities of acetate appear in peripheral blood (Annison, Hill & Lewis, 1957). A substantial glucose turnover in sheep has been indicated (Annison & White, 1961;Kronfeld & Simesen, 1961), focusing attention on the nature of glucose precursors in this species since very little glucose is absorbed from the alimentary tract. Propionate is well recognized as a source of glucose, but the possibility of butyrate and, to a less extent, of acetate being a precursor of glucose has been the subject of much speculation.…”
mentioning
confidence: 99%
“…One must suspect an overestimate, because with the single injection technique, this readily happens if too long a time-interval after injection is employed. 12 If this were the case, the point at 180 minutes after injection should be higher than the line of the preceding points.12 Contrary to this, it is clear in the originally published curves2s and in FIGURE 2, that the points at 180 minutes are not above the line, but rather right on it. The c w e s obtained from normal and ketotic cows and from normal sheep are regular, successive components are fairly clearly separated, and call for rather simpler calculations than those obtained from the rat.…”
mentioning
confidence: 88%
“…This has been done in normal and fasting sheep and in a few cases of pregnancy toxemia. [11][12][13] Ranges of values for the glucose pool size and inflow rate are giwn in TABLE 1. Pool size ttnd inflow rate both increased during pregnancy, especially during the last few days.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The demand of the lactating mammary gland for glucose (Annison and Linzell 1964;Bergman and Hogue 1967) is such that gluconeogenesis is greatly increased during lactation. On the other hand, the rate of gluconeogenesis is depressed during food restriction (Kronfeld and Simesen 1961;Steel and Leng 1968), suggesting that the lactating ewe SUbjected to feed restriction would serve as a particularly useful model for studying the control of gluconeogenesis in the ruminant. We have used this model to examine the extent to which body tissues may be mobilized to maintain glucose in circulation and have monitored the hormonal changes which occur in the lactating ewe in response to feed restriction.…”
Section: Introductionmentioning
confidence: 99%